Understanding E-Commerce Purchase Drivers in Southeast Asia: The Case of Digital Marketing, Brand Image, and E-WOM on ZALORA in Brunei and Malaysia - Nur Amalina Hj Roslan Roslan; Muhammad Faizal Azmi Azmi; Aisyah Binti Rahman Rahman; Daniel Lim Wei Jie Jie (ICON Publisher, 2024)
The purpose of this study was to examine and analyze the effect of Digital Marketing, Brand Image, and E-Wom on Purchase Intentions at the ZALORA marketplace in Brunei and Malaysia. Data collected using a questionnaire through the Google Form. The sample used amounted to 110 respondents. Methods of data analysis include descriptive analysis and quantitative analysis using multiple linear regression. The results of this study found that: (1) Digital marketing, brand image, and e-WOM have a positive and significant impact on purchase intention at the ZALORA marketplace. (2) Digital marketing has a positive and significant effect on purchase intention on the ZALORA marketplace. (3) Brand Image has a negative and significant effect on purchase intention on the ZALORA marketplace. (4) E-wom has a positive and significant effect on purchase intention on the ZALORA marketplace.